Health and ritual in Morocco : conceptions of the body and healing practices - Mateo Dieste, Josep Lluis, 1968- (Social, Economic and Political Studies of the Middle East and Asia, 2013)
In Health and Ritual in Morocco , Josep Lluis Mateo Dieste analyzes the many notions of the body that appear in various Moroccan medical and religious systems. Viewing these issues from anthropological and historical perspectives to the development of Islamic medicine in Morocco, this study highlights the elements of power that define these representations and practices. Mateo Dieste shows that most of the healing rituals challenge the strict division between physical and mental afflictions. Health and Ritual in Morocco provides a valuable structure for understanding Moroccan conceptions of the person, rites of passage, gender differences, and reproductive practices. It offers insights into the weight of the notions of impurity and purification of the body in the daily life of the contemporary Moroccan population.